Molière Portrayed with Puppets - Vigato, Teodora (Molière u hrvatskoj kulturi, 2024)
In this paper, the author explores the possibilities of presenting Molière’s work through the use of puppets. Using the example of Molière’s comedy- ballet The Imaginary Invalid, directed and scenographed by Zlatko Bourek, the author delves into the provocative poetics of the grotesque and the ugly as active participants in the theatrical act since the expressive visual artistry and exaggerated physicality of Bourek’s puppets emerge as conveyors of ideas within Molière’s work. A particular emphasis is placed on the worldview of the piece through the concept of Bourek’s “theater of monsters.” On the other hand, in the comedy, the author identifies lazzi, stage games, and thickening techniques that form the basis of puppetry dramaturgy. The author finds the elements of commedia dell’arte in Molière’s comedy, which distances it from courtly art but simultaneously brings it closer to a folk, or puppetry, expression. Molière didn’t create real men and women but rather “types” arising from the accumulation of accentuated traits, and a puppet itself is more of a “type” than a character. The puppet performance of The Imaginary Invalid and Bourek’s puppets are examined in the context of adult puppet theater (Figurentheater) and puppetry performances of Molière’s dramas in European puppetry.